Diabetic Ketoacidosis Revealing a Severe Hypertriglyceridemia and Acute Pancreatitis in Type 1 Diabetes Mellitus - Fatima Zahra Zaher; Imane Boubagura; Sana Rafi; Ghizlane Elmghari; Nawal Elansari (Case Reports in Endocrinology)
Diabetic ketoacidosis (DKA) is a life-threatening acute metabolic complication occurring in patients with diabetes, especially in patients with type 1 diabetes (T1D), due to an insulin deficiency. Moderate hypertriglyceridemia is commonly observed in DKA but severe hypertriglyceridemia with a triglyceride level exceeding 10g/L is very rarely reported. We report a case of a 14-year-old boy who had type 1 diabetes for 4 years treated with insulin therapy, also having adrenal insufficiency treated with hydrocortisone who presented with ketoacidosis and excruciating abdominal pain. Investigations revealed hypertriglyceridemia at 64g/L, lipasemia at 1000 U/L, and stage E pancreatitis on abdominal CT. The patient was treated with intravenous insulin, rehydration, and fenofibrate with good clinical and biological evolution. Severe hypertriglyceridemia causing pancreatitis in type 1 diabetes mellitus is a rare but very serious complication of DKA in children.